2015
DOI: 10.1093/gbe/evv074
|View full text |Cite
|
Sign up to set email alerts
|

The Magellania venosa Biomineralizing Proteome: A Window into Brachiopod Shell Evolution

Abstract: Brachiopods are a lineage of invertebrates well known for the breadth and depth of their fossil record. Although the quality of this fossil record attracts the attention of paleontologists, geochemists, and paleoclimatologists, modern day brachiopods are also of interest to evolutionary biologists due to their potential to address a variety of questions ranging from developmental biology to biomineralization. The brachiopod shell is a composite material primarily composed of either calcite or calcium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 76 publications
(100 reference statements)
6
55
0
Order By: Relevance
“…This probably indicates loss of these genes in the phoronid lineage, although we cannot exclude the possibility of misannotation. To explore the origin of mineralized tissues in lophophorates, we compared biomineralization-related genes among phoronids and brachiopods, including the mantle transcriptome of the brachiopod Magellania venosa 54 . We found only five shell matrix protein genes that are shared by Phoronis, Lingula and Magellania (Supplementary Fig.…”
Section: Lineage-specific Expansion Of Innate Immune Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This probably indicates loss of these genes in the phoronid lineage, although we cannot exclude the possibility of misannotation. To explore the origin of mineralized tissues in lophophorates, we compared biomineralization-related genes among phoronids and brachiopods, including the mantle transcriptome of the brachiopod Magellania venosa 54 . We found only five shell matrix protein genes that are shared by Phoronis, Lingula and Magellania (Supplementary Fig.…”
Section: Lineage-specific Expansion Of Innate Immune Genesmentioning
confidence: 99%
“…Notably, most of these genes can also be found in other metazoans with functions other than biomineralization. We failed to find brachiopod-specific shell matrix proteins in the Phoronis genome (Supplementary Table 36) 11,54 . Thus, our findings suggest that lineage-specific gene expansions, acquisition of novel genes and redeployment of extracellular matrix genes are involved in the evolution of lophophorate biomineralization.…”
Section: Lineage-specific Expansion Of Innate Immune Genesmentioning
confidence: 99%
“…Indeed, FAM20C is a kinase that phosphorylates the majority of the phosphoproteome in the extracellular matrices of bones and teeth, constituting a key player in vertebrate biomineralization processes [66]. Other recent investigations have revealed the presence of FAM20C-containing protein in the shell matrix of the giant limpet Lottia gigantea [48] and of the brachiopod Magellania venosa [58]. The presence of such a key protein, regulating the biomineralization formation of vertebrates in the shell matrices of molluscs and brachiopods reinforces the idea of a common molecular machinery, supporting the scenario of a conserved biomineralization toolkit between different metazoan lineages.…”
Section: Are Metazoan Shell Matrix Proteins Deeply Conserved?mentioning
confidence: 99%
“…Other studies have identified major conflicts between molecular and morphological phylogenetic analyses of extant brachiopod species (Saito et al 2001, Bitner & Cohen 2015. Genomic (Stechmann & Schlegel 1999, Helfenbein et al 2001, Endo et al 2005, Adachi et al 2013, Luo et al 2015 and, more recently, proteomic (Immel et al 2015, Jackson et al 2015) studies, as well as studies of gene expression in brachiopod species, are now being tackled, with exciting, compelling results (Altenburger et al 2011, Passamaneck et al 2015. Establishing relationships between genetic variation, gene expression, and morphology is the next frontier in linking geological and biological approaches to the study of brachiopod evolution.…”
Section: Populations and Species: Microevolutionmentioning
confidence: 99%
“…I suspect that as more genomic and combined morphological and molecular analyses (Wiens 2009, Giribet 2010, Reeder et al 2015 are conducted, past results that appeared to be in conflict will be better resolved. Phylogenomic studies (Kocot et al 2013, Nesnidal et al 2013, Jackson et al 2015, Lemer et al 2015, Luo et al 2015 will also help clarify these disagreements, and allow us to interpret results with greater confidence than is possible at this time.…”
Section: Phylogenymentioning
confidence: 99%